Development of the multi-criteria model for the quality of life assessment in local governments - Snežana Mijailović; Sanja Marković (Economic Themes, 2022)
The perception of satisfaction with the quality of life by an individual in urban and rural areas includes a number of objective and subjective indicators, based on the analysis that could be performed. Measuring the preferences of individuals living in different environments, in terms of life goals, needs, moods, expectations, as well as personal satisfaction with the quality of life, requires more criteria to be included for its evaluation. The research was conducted on the basis of twenty indicators for measuring the quality of life in local governments depending on the preferences of individuals, and of different age, gender, education, social status, and satisfaction motives. The subject of this paper is the selection of criteria in a multi-criteria model for assessing the quality of life in local governments, using adequate statistical tools. In addition to descriptive statistics and testing the significance of differences, the authors of the paper used a modified PROMETHEE multi-criteria method for ranking local governments.
Keywords: C44; C82; R58; 330; quality of life assessment; local governments; multi-criteria model; quality of life indicators; preferences of individuals; Promethee method